2000
DOI: 10.1207/s15327914nc372_12
|View full text |Cite
|
Sign up to set email alerts
|

Carrageenan Gel and Aberrant Crypt Foci in the Colon of Conventional and Human Flora-Associated Rats

Abstract: Carrageenans (CAR) are sulfated polymers from seaweed used as gelling agents in foods. Chemical carcinogen induction of tumors in the colon of rats is enhanced by CAR. We speculated that gut microflora is involved in this effect. We thus studied the initiating and promoting effects of undegraded CAR-kappa (345,000 mol wt) in conventional rats and in germ-free rats associated with a human fecal flora. The initiating effect of CAR was studied by scoring aberrant crypt foci (ACF) in the colon of Fischer 344 rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…This confounds interpretation of the data about promotion. Also, Taché et al (2) did not provide details about the actual composition of the microflora in their experimental rats, and we do not know if it was consistent throughout the experiment. Hence, these data cannot be used to declare that the colon cancer-promoting effect of foodgrade carrageenan is a "rodent-specific phenomenon" and that it requires a rodent intestinal microbiologic flora.…”
Section: Carrageenan In Foods: Responsementioning
confidence: 82%
See 1 more Smart Citation
“…This confounds interpretation of the data about promotion. Also, Taché et al (2) did not provide details about the actual composition of the microflora in their experimental rats, and we do not know if it was consistent throughout the experiment. Hence, these data cannot be used to declare that the colon cancer-promoting effect of foodgrade carrageenan is a "rodent-specific phenomenon" and that it requires a rodent intestinal microbiologic flora.…”
Section: Carrageenan In Foods: Responsementioning
confidence: 82%
“…One concern has focused on the potential for degraded (low molecular weight) carageenan to be formed by acid hydrolysis in the stomach and the possibility that this material could promote cancer of the colon (1). Rats fed degraded carrageenan have been shown to develop colorectal tumors (2). Studies involving initiation with the genotoxic carcinogen azoxymethane, followed by quantitation of the number of aberrant intestinal crypts formed in response to subsequent carrageenan exposure, have also suggested that degraded carageenan has the potential to promote colon cancer in rats (3).…”
mentioning
confidence: 99%
“…Carthew has raised issues pertaining to the role of human intestinal flora on the effects related to carrageenan and the possibility of interspecies variation in the toxicity of carrageenan. The paper by Taché et al (2) referred to by Carthew actually supports concerns about the availability of degraded carrageenan after exposure to food-grade carrageenan and human microflora. The authors report data on the average molecular weight of carrageenan recovered from stool samples in feeding experiments with rats in which human intestinal microflora had been introduced.…”
Section: Carrageenan In Foods: Responsementioning
confidence: 92%
“…The animals were fed with standard water and food ad libitum. Rats were divided into 4 groups; 1-CNT group (Control group, n=8): Normal sterile saline solution was administered (SID) by gastric lavage during 18 weeks, 2-HLF group (Halofuginone group, n=10): HLF (0.4 mg/kg, SID, Halocur ® oral sol., MSD Animal Health, France) was administered by gastric lavage during 18 weeks (Abramovitch et al, 2004), 3-CAN group (Cancer group, n=10): Azoxymethane (15 mg/kg, SigmaAldrich, St. Louis, MO, USA) was administered intraperitoneally once a week for 2 weeks to induce ACF (Morishita et al, 1997;Tache et al, 2000), and 4-CAN+HLF group (n=10). Azoxymethane was administered intraperitoneally at 15 mg/kg once a week for 2 weeks to induce ACF.…”
Section: Methodsmentioning
confidence: 99%